Genetic diversity of Aegilops Tauschii populations in Armenia - N. A. Hovhannisyan; A. H. Yesayan (ՀՀ ԳԱԱ հրատ.)
The goal of this study was to assess the level of genetic diversity of wild Aegilops tauschii by means of RAPD markers.15 RAPD primers generated total of 84 different sized fragments (loci) from DNA of 10 accessions of Aegilops tauschii, of which 79 markers were polymorphic over all accessions. The results obtained will allow to select genetically rich germplasm for sustainable ex situ conservation of studied populations. Հետազոտության նպատակն էր RAPD մարկերների կիրառմամբ գնահատել Aegilops tauschii պոպուլյացիաների գենետիկական բազմազանությունը: 15 RAPD պրայմերների կիրառմամբ 10 հետազոտված պոպուլյացիաների ԴՆԹ-ներից ամպլիֆիկացվել է ԴՆԹ-ի 84 հատված, որոնցից 79-ը պոլիմորֆ էին: Ստացված արդյուքնները թույլ կտան ընտրելու և ex situ պայմաններում պահպանելու առավել հարուստ և բազմազան գենետիկական նյութ: Целью данного исследования было изучение генетического разнообразия популяций Aegilops tauschii с применением RAPD маркеров. С помощью 15 RAPD праймеров из ДНК 10 исследуемых популяций было амплифицировано 84 фрагмента, из которых 79 оказались полиморфными. Полученные результаты позволят отобрать для ex situ сохранения генетически богатый и разнообразный материал.
Keywords: Biology; Biological Diversity; Genetics